A RARE CASE OF BOTRYOMYCOSIS IN AN IMMUNOCOMPETENT PATIENT - Khan, Sulhera; Shah, Nazish; Talat, Humaira; Mirza, Reema; Mala Ahuja, Pasph (Journal of Ayub Medical College Abbottabad, 2025)
The term botryomycosis is a misnomer meaning bunch of grapes and fungal infection. It is a chronic, granulomatous infection caused by the bacteria with only a few cases reported worldwide. We present a case of cutaneous botryomycosis in an immunocompetent patient which was identified on histopathology. The culture showed growth of Staphylococcus aureus which was sensitive to oral and intravenous antibiotics. The patient was started on oral linezolid and the lesions improved significantly without the need of surgical debridement and amputation. Botryomycosis serves as a diagnostic dilemma as the disease mimics other disorders like actinomycetoma, eumycetoma, scrofuloderma and nocardiosis. Therefore, it is important to consider botryomycosis as a differential in chronic suppurative infections even in immunocompetent hosts.